Optimasi temperatur udara pengering dan laju alir umpan pada proses pengeringan ragi roti - Ronny Purwadi; N Nicko; Patricia Stephanie (Jurnal Teknik Kimia Indonesia, 2009)
Dry-air temperature and feed flow rate optimization in the yeast drying process.The production of active dry yeast was studied in this work. The drying process was carried out in a spray dryer (EYELA © Spray Dryer SD-1) with particle flow was in the same direction with dry-air flow. Feed (18-20 %-w) was fed with rate of 100-200 mL/h and dry-air temperature of 70-90 °C was set to achieve the highest cell activities of dry yeast. The yeast activities were defined as cell viability and vitality. Viability is the number of living cell which was determined by cell counting under microscope using the staining technique, while vitality is the number of vital cell which could reproduce on an agar plate. The results show that temperature as well as feed-rate significantly affects yeast activities. Temperature effect is quadratic to yeast activities while feed-rate effect is linear. In the range of experiment conditions, the optimum condition was achieved with dry-air temperature of 70 °C and feed-rate of 200 mL/h. The dry yeast produced in optimum condition gave water content of 2-7% which was still similar with the water content of commercial yeast (2.4%).Keywords: dry yeast, S. cerevisiae, drying, spray-dryer, viability, vitality AbstrakProses pengeringan ragi dalam produksi ragi kering aktif dilaksanakan dalam penelitian ini. Pengeringan dilaksanakan dalam spray-dryer (EYELA © Spray Dryer SD-1) dengan aliran partikel searah aliran udara pengering. Laju alir umpan (18-20 %-berat) sebesar 100-200 mL/jam dan temperatur udara pengering antara 70-90 °C divariasikan dengan tujuan untuk mendapatkan ragi yang memiliki keaktifan maksimum. Keaktifan ragi dinyatakan sebagai viabilitas yaitu jumlah sel hidup, dan vitalitas yaitu jumlah sel yang dapat berkembang biak. Viabilitas ditentukan dengan cara menghitung sel pada counting chamber di bawah mikroskop melalui teknik pewarnaan (staining), sedangkan vitalitas ditentukan dengan menghitung sel vital yang dapat tumbuh kembali pada media pertumbuhan agar. Hasil percobaan menunjukkan bahwa baik temperatur udara pengering maupun laju alir umpan memberikan pengaruh yang signifikan terhadap aktivitas ragi. Temperatur memberikan pengaruh yang kuadratik sedangkan laju alir umpan memberikan pengaruh yang linier terhadap vitalitas ragi. Dalam rentang percobaan, kondisi optimum dicapai pada temperatur 70 °C dan laju alir umpan 200 mL/jam. Kondisi ini menghasilkan ragi kering dengan kandungan air antara 2-7%, dan cukup mirip dengan kandungan air ragi kering komersial (2,4%).Kata Kunci: ragi kering, S. cerevisiae, pengeringan, spray-dryer, viabilitas, vitalitas